'There is Nothing Post-Colonial about It' An interview with Indra Sinha - Ipekci, Yesim (Routledge Journals, Taylor & Francis Ltd, 2024)
This interview with the writer Indra Sinha, conducted in Toulouse, France in June 2017 and reworked in January 2020, is a product of my research on the relatively recent theoretical endeavour to interrogate the relationship between postcolonial and ecocritical studies. Indra Sinha's fictional and non-fictional works have substantially contributed to the international visibility of human and environmental injustices around the world, suggesting his potential engagement with the relationship between these two theoretical frameworks. In the interview conducted within this context, Sinha's debut novel Animal's People (2007), shortlisted for the 2007 Man Booker prize, is discussed as a postcolonial eco-socialist work offering a fictitious account of neo-colonial practices in India. The novel, particularly as the literary representation of the Bhopal disaster, sheds light upon the continuous destruction of human and non-human beings in postcolonial lands under neo-colonial policies. Yet, Sinha's ardent problematization of 'postcolonialism' as a label in particular, and of all labels in general for delineating literary works, complicates, albeit fruitfully, the course of the interview and our discussion of new theoretical frameworks emerging out of postcolonial theory. His responses on this issue are powerful statements calling for a particular focus on, if any -isms deemed necessary, transnational capitalism and 'traditional old-fashioned extortionism' instead of postcolonialism.
Keywords: Animal's people; Bhopal disaster; labelling; postcolonial ecocriticism; postcolonialism; Sinha; Indra